Caracterización de salud oral en escolares. Sector 2. Riobamba, 2021 - Carrion Mendoza, Wilson Anibal (2022)
ABSTRACT: This research aimed to analyze the students' level of knowledge of sector 2 of Riobamba, teachers, and parents in charge of their upbringing. The work methodology was descriptive and cross-sectional, and the population was students legally enrolled in the parallels of the academic units of sector 2 of Riobamba. The technique used for the study was the survey. The data collection instrument was the clinical history form 033 validated by the Ministry of Public Health. With the information reported in the document, the DMFT caries index for permanent dentition was calculated, Ceod caries for primary dentition, and O'Leary's plaque index. The results determined a lousy knowledge for students and regular for teachers. In addition, there was no relationship between the feeding with the DMFT index (p=0.00) and the Ceod index (p=0.00). It was concluded that the level of the DMFT index was of shallow risk in 61% of the population. The same happened with the Ceod index. The trouble was very low in 43% of the people, while the level of the plaque index was acceptable in 79% of schoolchildren. Keywords: CPOD, Ceod, Plaque index No: